Rapid diagnosis of ETEC and HPI-harboring Escherichia coli infection in newborn piglets with diarrhea - Cheng Darong; Zhu Shan Yuan; Chen Xiao Lang; Gao Xiao Pan; Ding Wen Wei; Sun Huai Chang (African Journal of Pig Farming, 2014)
Diarrhea is a common and important disease in industrial pig farms and the pathogenic Escherichia coli infection is the main cause of morbidity and mortality in newborn piglets. The preliminary diagnoses on this disease are mainly depending on clinical symptom and detailed body dissection. To further shorten the diagnosis time and increase the determination efficiency for newborn piglet diarrhea caused by E. coli, a rapid method was established based on the fast bacterial culturing followed by the PCR examining for the virulence factor genes, such as enterotoxin ST1, ST2, LT1 and high pathogenicity island (HPI). A total of 151 rectal swab samples were obtained from live diarrheic piglets from Jiangsu province, China. Following the first cultivation in LB broth at 37°C for 6 h, all the samples were detected by the PCR methods, and the data show that 95 cases (62.91%) were infected with HPI-harboring E. coli, 24 cases (15.89%) were infected with Enterotoxigenic E. coli (ETEC) and 14 cases (9.27%) were infected with ETEC and HPI-harboring E. coli. In addition, 2660 bacteria isolates were picked from all the 133 bacterial cultures which contained HPI-harboring E. coli and/or ETEC and the data of PCR examination determined that only 57 isolates were HPI-harboring E. coli, 20 were ETEC and 3 were both ETEC and HPI-harboring E. coli. This research not only revealed that HPI-harboring E. coli and ETEC are the prevalent pathogen of newborn piglet diarrhea, but also suggested that the method used in this study is specific, easier and more rapid to perform in the diagnosis of the infection of diarrheagenic E. coli with high accurate rate than the bacterial isolation and identification.